Decreased brain-derived neurotrophic factor expression in chronic kidney disease: integrated clinical and experimental evidence - Chen, Juan; Fu, Lili; Li, Mengjin; Xie, Kun; Li, Xinming; Zhou, Xu-jie; Yang, Li; Zhang, Liming; Xue, Cheng; Mao, Zhiguo (Frontiers in Molecular Biosciences, 2025)
BackgroundChronic kidney disease (CKD) is a progressive disorder characterized by declining renal function and systemic metabolic disturbances. Brain-derived neurotrophic factor (BDNF), a key member of the neurotrophic family, plays critical roles in neuronal function and muscular metabolism. However, the evidence and regulatory mechanisms underlying decreased BDNF levels in CKD remain inconclusive.MethodsThis study systematically evaluated circulating BDNF alterations in CKD patients through a meta-analysis of clinical studies involving 1,549 participants, complemented by experimental validation in unilateral ureteral obstruction (UUO) mice and single-cell transcriptomic database analysis to investigate tissue-specific BDNF protein expression and regulatory patterns.ResultsMeta-analysis confirmed significantly reduced circulating BDNF in CKD patients (WMD = −0.62 ng/mL, 95% CI [-0.98, −0.25], P < 0.001; I2 = 87%). In 14-day UUO mice, renal immunohistochemistry (IHC) showed significantly reduced BDNF expression (P < 0.001), which was further validated by Western blot analysis demonstrating a progressive decline in BDNF protein levels from day 14 to day 21 post-obstruction. Single-cell mRNA sequencing further confirmed that Bdnf levels were lower in renal proximal tubule (PT) cells, macrophages (Mφ), and podocytes in UUO mice compared to normal controls, Additionally, Bdnf-as—a long non-coding RNA known to epigenetically repress BDNF—was significantly upregulated in proximal tubules of CKD patients based on human transcriptomic data. This upregulation was validated in UUO mice by qPCR, showing a time-dependent increase in Bdnf-as expression at days 14 and 18 post-obstruction.ConclusionThis study integrated meta-analysis, murine model validation, and single-cell transcriptomic profiling to demonstrate a significant reduction of BDNF in CKD. Furthermore, renal BDNF expression decreased locally, predominantly originating from proximal tubule cells, macrophages, and podocytes, possibly epigenetically inhibited by the upregulation of lnc RNA Bdnf-as.